Improving the ischemia-reperfusion injury in vascularized composite allotransplantation: Clinical experience and experimental implications - He, Jiqiang; Khan, Umar Zeb; Qing, Liming; Wu, Panfeng; Tang, Juyu (Frontiers in Immunology, 2022)
It is still unclear between ischemia-reperfusion injury and transplant outcome in vascularized composite allotransplantation (VCA). The experience is based on solid organ transplants.The previous publications have not clearly described the relationship between the tissue damage and ischemia time, nor the rejection grade. In this review, we found that the rejection episodes and rejection grade are usually related to the ischemia time, both in clinical and experimental aspects. Moreover, we summarized the potential therapeutic measures to mitigate the ischemia-reperfusion injury.